Mutation Mapping of PD-L1 Expression in Advanced Non-small Cell Lung Cancer: A Real-world Retrospective Cohort Study - Hao, Fang; Ma, Qing; Zhong, Diansheng (Combinatorial Chemistry & High Throughput Screening, 2025)
IntroductionThe duration of response to immune checkpoint inhibitors (ICIs) varies because of tumor immune heterogeneity, and employing programmed death receptor ligand 1 (PD-L1) expression to evaluate the efficacy of anti-programmed cell death-1 (PD-1)/PD-L1 antibodies remains controversial.MethodsA total of 138 advanced non-small cell lung cancer (NSCLC) patients were subdivided into 2 groups - 52 patients with a PD-L1 Expression≥50% and 86 patients with a PD-L1 Expression <50% - based on next-generation sequencing (NGS) to analyze multiple-dimensional data types, including tumor mutation burden (TMB), gene alterations, gene enrichment analysis, therapy response, and immune-related adverse events (irAEs).ResultsHigh levels of PD-L1 expression were significantly associated with advanced age and TMB status. The PD-L1≥50% cohort presented mutations of KRAS, NOTCH1, and FAT, while the PD-L1<50% group exhibited mutations of EGFR, PTEN, or LATS1/2. Except for the ascertained DNA damage response regulation. Even though there was no significant difference between PD-L1≥50% and PD-L1<50% cohorts on therapy response, patients with a PD-L1 Expression≥50% elicited a high irAEs incidence rate and increased plasma interleukin 6 (IL-6) concentration.ConclusionThis real-world retrospective study suggested that high expression of PD-L1 exhibited inappropriate activation of different pathways and collaborated with anti-cytokines and chemokines therapy may optimize clinical therapy efficacy.
Keywords: next-generation sequencing